Simple Multi Attribute Rating Technique to Determine Resignation of Prospective New Students - Lidya Wati; Sovia Bella; Mansur Mansur (Institute of Computer Science (IOCS), 2021)
Prospective new students will apply to one or more of the colleges, and choose more than one major. Prospective new students who are declared to have passed more than one university will choose a better college, and will withdraw from other universities. Universities that are not re-registered will suffer losses and must look for other prospective new students. So a decision support system for the resignation of prospective new students was built using the Simple Multi Attribute Rating Technique (SMART) method by selecting the criteria and weight stages, to determine the factors supporting the decision. The criteria used to build this system are grades, parents' income, majors and location. This decision support system can assist the staff of the new student admissions committee in obtaining data in the form of a list of prospective new students who re-register and resign. Based on the results of testing on the system, the accuracy value is 86.96%. So it can be concluded that this system has been able to be used for the selection of prospective new students.